Genetic, morphological and chemical investigations reveal the genetic origin of Pompia (C. medica tuberosa Risso & Poiteau) – An old endemic Sardinian citrus fruit. (December 2019) - Luro, François; Viglietti, Grazia; Marchi, Elodie; Costantino, Gilles; Scarpa, Grazia Maria; Tomi, Felix; Paoli, Mathieu; Curk, Franck; Ollitrault, Patrick
Abstract: Citrus fruits have been introduced to the Mediterranean area from Asia for centuries and spontaneous crosses have generated several hybrid forms, some of which have had agricultural or industrial success while others have remained niche food or ornamental products, or have disappeared. Pompia ( C. medica tuberosa Risso & Poiteau) is an old endemic citrus fruit from Sardinia of unknown genetic origin. Initial phenotypic and molecular characterizations revealed a high degree of similarity with lemon ( C. limon (L.) Burm.) and citron ( C. medica L.). To identify the ancestors of Pompia, 70 citrus species of the Citrus genus were genotyped with 36 codominant molecular markers (SSR and InDel) of nuclear and cytoplasmic genomes. Diversity analysis and allelic comparisons between each citrus species at each locus indicated that Pompia resembles lemon and limonette of Marrakech, i.e. the result of a cross between sour orange ( C. aurantium L.) and citron, where citron was the pollinator. Two Italian citron varieties were identified as potential male parents, i.e. Diamante and Common Poncire. However, we were unable to differentiate varieties of sour oranges because varietal diversification in this horticultural group resulted from DNA sequence variations that SSR or InDel markers could not reveal. Rhob el Arsa and Poncire de Collioure were found to be two synonyms of Pompia. Pompia appeared to be equally distinct from citron, lemon and sour orange based on the overall analysis of the fruit, leaf and seed phenotype, and juice chemical composition. At the leaf level, the Pompia essential oil (EO) composition is close to that of citron whereas the zest is much closer to that of sour orange. Graphical abstract: Pompia's parents found thanks to an investigation combining genetic, biochemical and phenotypic characterization. Image 1 Highlights: Pompia derived from a citron x sour orange cross. Citron is always the male parent of its hybrids, never the receptor (female). SSR markers genotyping is efficient to resolve genetic origin of citrus crops. It is difficult to elucidate citrus phylogeny based only on phenotypic characters. Pompia zest EO composition is relatively closer to that of sour orange than to citron.